Communication organization and implementation problems of the Lithuanian national museums - Šuminas, Andrius (Information & Media, 2015)
The aim of the article is to overview the peculiarities of organizing and implementing the communication of the Lithuanian national museums with an emphasis on the use of virtual museum presences. The paper presents the results of the research that contributed to determining the goals of communication of the Lithuanian national museums, defining their target audience, discussing in detail the processes of organizing and implementing museum communication. Moreover, the main problems faced by the museum staff in the communication activities are identified. Great attention is paid to the use of museum websites and interactive social media tools. The information necessary for the research has been collected by way of direct interviews with directors of the Lithuanian national museums or employees responsible for communication: Romualdas Budrys, Director of the Lithuanian Art Museum; Birutė Kulnytė, Director of the National Museum of Lithuania; Osvaldas Daugelis, Director of M. K. Čiurlionis National Museum of Art; and Ramunė Hazir, PR Manager at the National Museum – Palace of the Grand Dukes of Lithuania.